2020
DOI: 10.3390/ijerph17051520
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Regional Distribution Equity among Doctors in China before and after the 2009 Medical Reform Policy: A Data Analysis from 2002 to 2017

Abstract: Background: Although China began implementing medical reforms in 2009 aimed at fair allocation of the regional distribution of doctors, little is known of their impact. This study analyzed the geographic distribution of doctors from 2002 to 2017. Methods: This study calculated the Gini coefficient and Theil index among doctors in the eastern, central, and western regions (Category 1) of China, and in urban and rural areas (Category 2). The statistical significance of fairness changes was analyzed using the Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
(28 reference statements)
1
21
0
1
Order By: Relevance
“…Another finding indicates that the causes of inequality in the eastern, central, and western regions principally came from the within-group rather than between-group rate. Compared to health resources, the Theil Index values of rehabilitation resources were higher; however, health resources, such as doctors, experienced the same declining trend during the same time period [ 16 ]. The level of economic development and amount of rehabilitation resources in the eastern provinces, such as Shanghai, Beijing, Tianjin, Guangdong, Jiangsu, and Shandong, were much higher than in other provinces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another finding indicates that the causes of inequality in the eastern, central, and western regions principally came from the within-group rather than between-group rate. Compared to health resources, the Theil Index values of rehabilitation resources were higher; however, health resources, such as doctors, experienced the same declining trend during the same time period [ 16 ]. The level of economic development and amount of rehabilitation resources in the eastern provinces, such as Shanghai, Beijing, Tianjin, Guangdong, Jiangsu, and Shandong, were much higher than in other provinces.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the research has deeply explored the following three topics: (1) specific rehabilitation issues such as cardiac rehabilitation [ 11 ], exercise-based rehabilitation for non-communicable diseases [ 12 ], community-based rehabilitation resources [ 13 ], etc. ; (2) health resource disparities including the perspectives of urban and rural communities [ 14 ], specific topics such as workforce [ 15 ] (physicians [ 16 ]), facilities [ 17 ] (institutions [ 18 ]), services, etc. ; and (3) research methods on disparity or equity, for example the Theil Index [ 19 ], Gini-coefficient [ 20 ], Atkinson index [ 21 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Being aware of the high conflict rate between doctors and patients in China, systemic managements and normalized media coverage and volunteerism have been performed to improve this situation [35][36][37]. How to protect doctors from injuries in the process of practicing has always been the attention of the whole society [21,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate distribution of health resources and equipment means that community members have equal access to healthcare services. It underlines equity in geographically defined populations; all healthcare equipment and resources should reasonably be apportioned based on health care requirements and needs of every individual in the community (6).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, fair health resources allocation is considered the most important aspect among the health assessment indicators used in more than 30 European regions. In addition, studies in many developing countries (e.g., Thailand, Vietnam, Bangladesh, and India) reported that health resources are unfairly allocated to regions and distributed among people of different ethnicities and income groups (6). Inequality in health is a general term used to show the current differences, changes, and inequities for individuals or groups in access to healthcare services.…”
Section: Introductionmentioning
confidence: 99%